2017
DOI: 10.4081/aiua.2017.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Blood platelet activity in men with vasculogenic erectile dysfunction

Abstract: Objective: The aim of this study was to investigate the platelet activity in patients with vasculogenic erectile dysfunction (ED). Materials and methods: The total blood count, including hemoglobin (Hgb), white blood cell (WBC), red blood cell (RBC), platelet (PLT) and mean platelet volume (MPV) parameters were measured in the patient (n = 70) and control groups (n = 50). Results: The average age was 48.1 ± 11.7 and 47.6 ± 12.3 in the patient and control groups (p = 0.8217), respectively. MPV was higher in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…They suggested that platelets may play a role in pathogenesis of vascular complications and MPV may help in the evaluation of disease progression (Ciftci et al, ). A recent study by Bayraktar & Albayrak detected significantly higher MPV levels in ED than controls (Bayraktar & Albayrak., ). On the other hand, Senturk and his colleagues detect nonsignificant difference in MPV values between patients and controls in their recent study (Senturk et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…They suggested that platelets may play a role in pathogenesis of vascular complications and MPV may help in the evaluation of disease progression (Ciftci et al, ). A recent study by Bayraktar & Albayrak detected significantly higher MPV levels in ED than controls (Bayraktar & Albayrak., ). On the other hand, Senturk and his colleagues detect nonsignificant difference in MPV values between patients and controls in their recent study (Senturk et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Platelet volume depletion occurs due to platelet activation and its discharge from the granules. Since platelet activation and consumption are associated with a decrease in peripheral blood Plt, therefore, bone marrow activity and the presence of immature platelets in the blood are inevitable, leading to an increase in PDW (Bayraktar & Albayrak, ; Tang et al, ). Studies of platelet disorders in people with anxiety indicate defects in the serotonin transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred and sixty patients had a detailed clinical investigation including medical history and physical examination, laboratory investigations, nocturnal penile tumescence assessment (NPT), penile color Doppler ultrasonography (pDUS), and neurophysiological tests (NT) (Figure 1). Healthy controls did not undergo NPT and pDUS.…”
Section: Methodsmentioning
confidence: 99%